A New Sample Preparation System for Micro-14C Dating of Glacier Ice with a First Application to a High Alpine Ice Core from Colle Gnifetti (Switzerland). Issue 2 (8th November 2017) - Hoffmann, Helene; Preunkert, Susanne; Legrand, Michel; Leinfelder, David; Bohleber, Pascal; Friedrich, Ronny; Wagenbach, Dietmar
Abstract: Radiometric dating of glacier ice is an essential tool where stratigraphic dating methods cannot be applied. This study focuses on Alpine glacier ice and presents a new sample preparation system for dating of glacier ice samples via radiocarbon ( 14 C) dating of the microscopic particulate organic carbon (POC) fraction incorporated in the ice matrix. An adaptable, low-cost inline filtration-oxidation-unit (REFILOX) has been developed, which for the first time unifies all sample preparation steps from ice filtration to CO2 quantification in one closed setup. A systematic 14 C investigation of modern European aerosol samples revealed that a POC combustion temperature of 340°C provides the best representation of the real sample age. A very low process blank of maximally 0.3±0.1 µgC now enables 14 C dating of high Alpine ice samples, where POC concentrations are generally low (typically 10–50 µgC/kg), in an ice sample mass range of 300–500 g. In a first successful application, the method was used to obtain age constraints for an ice core from the cold, high Alpine firn saddle Colle Gnifetti (Switzerland). Analysis of the bottom ice core sections revealed a basal age of 4171–3923 cal yr BP but also a so far enigmatic discontinuity in the age-depth relationship.